Hidroesterificación de Aceite Usado de Cocina con Agua Subcrítica y Etanol Supercrítico para la Producción de Biodiésel - Quiroga Pérez , Walter; Guzmán Beckmann, Liliana; Chico Proaño, Andrés; Reyes-Narváez, Emerson (EASI: Engineering and Applied Sciences in Industry, 2023)
The objective of this study was to determine the best combination of experimental factors of temperature and reaction time for the two-step hydroesterification reaction (hydrolysis and esterification) of used cooking oil with subcritical water and supercritical ethanol, which allows maximizing the obtaining of ethyl fatty acid esters (biodiesel). The used oil (raw material of the process) was characterized by physicochemical tests applicable to oils and fats of animal and vegetable origin. The hydrolysis reaction was carried out with a 3x3 factorial experimental design in temperature and time (250, 275 and 300 °C for 20, 40 and 60 minutes), with a constant 1:1 water-oil volumetric ratio. The free fatty acids were separated from glycerin, they were esterified with supercritical ethanol based on a 3x3 factorial experimental design in temperature and time (250, 300 and 350 ° C for 10, 20 and 30 minutes) keeping the pressure of the medium constant. reaction at 10 MPa and the molar ratio of ethanol - free fatty acids 10:1. The percentage conversion of free fatty acids from the hydrolysis reaction and the percentage conversion from the esterification reaction were determined by potentiometric titration.
Keywords: Hydroesterification; Hydrolysis; Esterification; Supercritical ethanol; Biodiesel